Development of high thermally conductive and electrically insulated epoxy nanocomposites with high mechanical performance. Issue 9 (26th May 2021) - Wang, Shuo; Cai, Rui; Xue, Hongqian; Liu, Tianqing; Han, Sensen; Zhou, Zhiqiang; Hu, Zonghao; Meng, Qingshi
Abstract: Developing polymer‐based nanocomposites with high thermal conductivity, mechanical performance, and electrical insulation becomes a huge challenge in both academia and industry. In this article, the synergistic effects of boron nitride (BN) nanosheets and carbon nanotubes (CNTs) on mechanical properties and thermal conductivity of epoxy nanocomposite adhesives were investigated. The results showed that the addition of one‐dimensional CNTs and two‐dimensional BN nanosheets into the epoxy matrix contributes to the formation of a three‐dimensional network and a larger contact surface between the nanofillers and the epoxy matrix. The hybrid filler of BN and CNTs provided significant improvements in thermal conductivity and mechanical properties of epoxy nanocomposite adhesives. At 1.06 vol% of BN‐CNTs, epoxy nanocomposite adhesives provide higher Young's modulus, fracture toughness ( K 1C ), energy release rate ( G 1C ), lap shear strength, and thermal stability compared with epoxy/BN nanocomposite adhesives. The thermal conductivity of epoxy/BN‐CNT nanocomposites recorded its maximum values of 0.49 K m −1 k −1 at 3.79 vol% and increased by 335% compared with 133% in case of epoxy/BN at the same fraction of 3.79 vol%.